Study of electrical properties in graphene oxide thin films as a transparent conductive material - Adekanmbi, Martins; Jonah-Iniebiye, Serian Ikiomoye; Amaechi, Chukwuwendu Jeffrey (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
Graphene oxide films were successfully prepared via the modified Hummer method. The deposition of the material was done by the spin coating method. The optical characterization (Ultraviolent (UV) spectroscopy) was carried out using a (UV 752) ultraviolet-visible-Near Infra-Red (UV-VIS-NI) spectrophotometer, at the wavelength interval of 250 nm to 1100 nm. The carrier density, carrier concentration, electrical conductivity, resistivity, sheet resistance, and mobility of graphene oxide as a transparent conducting material were investigated using the Hall Effect measurement. The results are shown in a table in this work. Profilometry results showed the thickness of these reduced graphene composite films ranging from 130 – 900nm, which shows that the more layers, the better transparency it produces.